conflicts in international teams - Kurdovanidze, Salome; Quigley, Martin John David; Habeeb Mohamed, Mag Mohamed Meeran Mohiadeen; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
This thesis aims to define international team and conflicts and identify the essential competencies for a manager and employee of international teams. It is argued that everyone in an international team should possess more skills and competencies than those who belong to homogeneous teams. As a result, representatives of international team must be able to understand culturally diverse backgrounds manage conflicts constructively, and comprehend different strategies to handle sensitive cases. The research begins by reviewing literature on culture, cultural dimensions in the team and conflict. A survey was performed on 167 individuals from various cultural backgrounds to analyze their attitudes towards multicultural teams and their managers. Some findings are in accordance with theories and some show different interesting opinions experienced pragmatically by the respondents. Eventually, the author based on the results obtained from the empirical research and the theoretical literatures has created a recommendation.
Vedoucí práce: Martin John David Quigley
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses